Public Knowledge about Wolbachia-Aedes Technology: A Survey among Cirebon City Residents, Indonesia - Herawati Herawati; Witri Pratiwi; Muhammad Hussein Gasem (GHMJ (Global Health Management Journal), 2025)
Background: Wolbachia-Aedes technology is one of the innovations in reducing dengue fever incidence in Indonesia. Its implementation may be limited by insufficient public knowledge, as low awareness can reduce community acceptance and participation in Wolbachia-Aedes technology, both of which are essential for the technology’s effectiveness. Aims: To determine the public knowledge about Wolbachia-Aedes technology and the associated factors in Cirebon City residents, Indonesia. Methods: This is an observational study with a cross-sectional approach that was conducted in Cirebon City Health Centers (Puskesmas) between June and July 2024, using a cluster random sampling technique. Cirebon City residents who visited Puskesmas and met the inclusion and exclusion criteria were recruited as samples. Data were collected through self-administered validated questionnaires. Results: There were 600 respondents, consisting of female (68%) who participated in the study. Most of the sample were senior high school graduates (68.2%). The results showed that 39.5% of respondents had poor knowledge, while 51.5% had moderate knowledge and 9% had good knowledge. Age [adjusted OR 1.86 (95%CI 1.32-2.63)] and education level [adjusted OR 2.12 (95%CI 1.38-3.27)] were the factors that related to public knowledge about Wolbachia-Aedes technology in Cirebon City, Indonesia. Conclusion: Most Cirebon City residents had moderate knowledge, with a substantial proportion still having poor knowledge regarding Wolbachia-Aedes technology. Older age and lower education levels were associated with poorer knowledge. The government needs to improve public knowledge about Wolbachia-Aedes technology before implementation through targeted health promotion, particularly for older populations and those with lower education levels.